Characterisation of a multijet plasma device by means of mass spectrometric detection and iCCD imaging. (9th October 2018) - Stancampiano, A; Selaković, N; Gherardi, M; Puač, N; Petrović, Z Lj; Colombo, V
Abstract: Atmospheric pressure plasma jets (APPJs) have been one of the most studied nonthermal discharges in the past decade. Recently, the use of multiple jets in order to cover larger areas has become desirable. However, the interaction between neighboring jets is a common phenomenon that can greatly modify plasma characteristics up to the point of merging several jets into a single one. The present study focus on bringing new insight on this phenomenon, named jet-to-jet coupling, investigating the discharge modes (coupled and uncoupled) of a plasma source composed of an array of seven plasma jets arranged adjacent to one another and driven by a sinusoidal excitation. The experimental results achieved by means of mass spectrometry, show a considerable increase in ion concentrations in the plasma, up to some orders of magnitude in the case of negative ions, as an effect of jet-to-jet coupling. Temporally resolved imaging of the discharge also shows how the evolution and intensity of the discharge are greatly affected by jet-to-jet interaction. Air/helium mole fraction and negative ions concentration are regarded as the main possible parameters affecting the coupling phenomenon. Moreover, experimental results suggest that the presence of remnant conductive channels behind the ionization fronts governs the propagation of the next ionization fronts, independently from the direction of propagation (from the source toward the target or vice versa). Furthermore, a parametrical investigation of the coupled mode discharge showed the presence of a critical value of the imposed voltage for which a drastic change in the electrical characteristics of the discharge is observed.